METHODOLOGICAL ASPECTS OF STRATEGIC MANAGEMENT OF ENTERPRISE DEVELOPMENT IN THE TRADE SPHERE - HRABOVSKA, Іryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the actual topic of strategic management of the development of the enterprise in the field of trade, the definition of the essence and the development of methodological aspects of the justification of the strategies of the development of the trade enterprise. The author characterizes the features of the functioning of trade enterprises in the modern economic environment. The relevance of setting and solving a special research task regarding the use of an individual strategic set for each studied subject of trade entrepreneurship when determining strategic directions for further development is proven. The article highlights the modern features of the functioning of the trade sector, which determine the requirements for substantiating enterprise development strategies, justifies the need to develop and identify general and basic business strategic alternatives, from which a trade enterprise will be able to create a strategic portfolio by combining them. Based on the analysis of approaches to organizing strategic choice, a classification of development strategies for a trade enterprise has been formed, taking into account the main stages of the enterprise's "life". The methodological principles of strategic management considered by the author allow to a large extent to compensate for the imperfection of the methodological base and the limited resources for the implementation of strategic planning, which lead to the loss of market opportunities and the deterioration of the competitive positions of Ukrainian enterprises in the trade sector. The principles and scientific approaches to the development of trade enterprise development strategies have been proposed, the mechanism for substantiating trade enterprise development strategies has been improved, which, unlike the existing ones, includes an analytical phase, a goal-setting phase, a strategic phase, which allows for the formation of a strategic portfolio of an enterprise in the trade sphere and a phase of monitoring, evaluating the implementation of the strategy and, if necessary, adjusting the action plan. The use of economic and mathematical modeling methods is proposed to study possible directions of enterprise development and select the most effective option for a development strategy, taking into account possible changes in external factors. The development of a competent development strategy is currently the most affordable way to increase the company's intangible assets, which are highly valued in modern business.
Keywords: strategic management; development strategy; trading company; sphere of trade; strategic planning; stages of the life cycle